Characterization of Selected Niger Delta Crude Oil Blends - PERETOMODE, Ebikapaye; PERETOMODE, Obiajulu; AKPOTU, Daniel; AKPOVI, Oyubu (ABUAD Journal of Engineering and Applied Sciences, 2025)
The process of determining a crude oil type’s chemical and physical characteristics is known as crude oil characterisation. The properties obtained from characterisation lay the foundation for crude commercial valuation, engineering design, upstream processes, downstream processes, and a better understanding of individual crude blends; hence the need for this study. The primary objective of the study was to experimentally determine five different Niger Delta crude blends from different terminals to understand, carefully characterise, and compute other parameters based on experimental data using ASTM procedures. These properties included API gravity and kinematic viscosity at elevated temperatures. The results show that the crudes are softly naphthenic to fairly paraffinic, with UOPK ranging from 11.4 to 12.1, with supportive VGC values that increase as molecular weight increases. Specific gravity increased with an increase in molecular weight and the mean average boiling point. The API gravity ranges from 18.65 to 47.45, and kinematic viscosity decreases at an increasing temperature of 50 °C. Agbami Light had the highest oAPI and the lowest estimated molecular weight of 168.050; Ebok crude had the lowest oAPI of 18.65 and the highest molecular weight of 301.684. The result shows a high content of sulphur at a lower API and a high specific gravity. This study has characterised the various crude oil blends, and the results show a clear relationship between the crude chemical properties.